(untitled) (De la Crítica, 2024)
Academic discourse is characterized by its precision, objectivity, impersonal atmosphere, and interest oriented more towards processes and objects than towards the agents of the processes. Spanish has passive reflex constructions and impersonal constructions with se, two similar and valuable resources to confer the characteristics that are proper to academic discourse. The aim of this study was to verify the effectiveness of the grammatical criteria of form, distribution, function and substitution to distinguish both constructions in a corpus of 33 abstracts from venezuelan academic journals focused on the humanities. The results show that the effectiveness of the criteria is relative, a preference for the use of reflex passive sentences, in which the verb or process takes a thematic role. It is concluded that there is a need to complement grammatical criteria with pragmatic ones such as the contextual nature of gender.